Exo‐exo synergy between Cel6A and Cel7A from Hypocrea jecorina: Role of carbohydrate binding module and the endo‐lytic character of the enzymes. Issue 8 (16th March 2017) - Badino, Silke F.; Christensen, Stefan J.; Kari, Jeppe; Windahl, Michael S.; Hvidt, Søren; Borch, Kim; Westh, Peter
ABSTRACT: Synergy between cellulolytic enzymes is essential in both natural and industrial breakdown of biomass. In addition to synergy between endo‐ and exo‐lytic enzymes, a lesser known but equally conspicuous synergy occurs among exo‐acting, processive cellobiohydrolases (CBHs) such as Cel7A and Cel6A from Hypocrea jecorina . We studied this system using microcrystalline cellulose as substrate and found a degree of synergy between 1.3 and 2.2 depending on the experimental conditions. Synergy between enzyme variants without the carbohydrate binding module (CBM) and its linker was strongly reduced compared to the wild types. One plausible interpretation of this is that exo‐exo synergy depends on the targeting role of the CBM. Many earlier works have proposed that exo‐exo synergy was caused by an auxiliary endo‐lytic activity of Cel6A. However, biochemical data from different assays suggested that the endo‐lytic activity of both Cel6A and Cel7A were 10 3 –10 4 times lower than the common endoglucanase, Cel7B, from the same organism. Moreover, the endo‐lytic activity of Cel7A was 2–3‐fold higher than for Cel6A, and we suggest that endo‐like activity of Cel6A cannot be the main cause for the observed synergy. Rather, we suggest the exo‐exo synergy found here depends on different specificities of the enzymes possibly governed by their CBMs. Biotechnol. Bioeng. 2017;114: 1639–1647. © 2017 Wiley Periodicals, Inc. Abstract : Synergy between the two cellobiohydrolases Cel6A and Cel7A in the hydrolysis of cellulose was investigated. Badino and co‐workers found that the degree of synergy (DS) was shown to be consistently stronger between wild types enzymes, than pairs of truncated enzymes without linker and CBM. The authors suggest different substrate specificities of the two cellobiohydrolases as the molecular interpretation of the observed exo‐exo synergy since hydrolysis of certain cellulose surface structures provides better substrate for the other.